Pengaruh Technology Acceptance Model Terhadap Pengambilan Keputusan Pembelian Pada Online Shop Grifabell - Ruth Patty (Jurnal Administrasi Bisnis, 2014)
AbstractThese days, technology are growing very fast, The use of technology has been widelyused in various sector. For example, in the fashion sector, also using technology asa medium to promote and to market the product. And with the increasing numberof Internet users, are expected to influence people’s behavior to make a purchasefrom conventional purchases to e-commerce.To realize a transaction or customerparticipation, it takes trust of each customer. In this study, the population is fromthe respondents who have ever made a purchase of shoes from Grifabell throughsocial media instagram. Data collection techniques used is through a survey using aquestionnaire, and questionnaires collected from a sample of 120 respondents whichhas been distributed through an Google Drive’s online questionnaire to Grifabell’scustomers throughout Indonesia. Before the data were analyzed, the authors testedthe validity and reliability of 30 samples using SPSS software.The research method used is multiple regression analysis and simple regression, Ftest, T test and determination coefficient. From these results, it can be concludedthat the indicators of variable technology acceptance model: the perceived qualityof e-shopping and attitude have a positive effect on the variable of trust, andthe indicators from confidence’s variables is experience, the quality of work, andintelligence which have a positive effect on the purchase decision variables.Keywords: Social Media, Technology Acceptance Model, Trust, PurchasingDecision, InstagramAbstrakPerkembangan teknologi saat ini sudah berkembang sangat pesat, pemanfaatanteknologi sudah banyak digunakan diberbagai bidang. Misalnya pada bidangfashion, yang memanfaatkan teknologi sebagai media untuk mempromosikan danmemasarkan produk. Dengan semakin banyaknya pengguna internet, diharapkandapat mempengaruhi prilaku masyarakat untuk melakukan pembelian, daripembelian secara konvensional ke e-commerce. Untuk mewujudkan transaksi ataupartisipasi pelanggan dibutuhkan kepercayaan dari tiap-tiap pelanggannya. Pada penelitian ini, populasinya adalah responden yang pernah melakukan pembeliansepatu Grifabell melalui media sosial instagram. Teknik pengumpulan data yangdigunakan adalah survei dengan menggunakan kuesioner, dan dari penyebarankuesioner terkumpul sampel sebanyak 120 responden yang telah disebarkan melaluikuesioner online Google Drive kepada pelanggan Grifabell di seluruh Indonesia.Sebelum dilakukan analisa data, penulis melakukan uji validitas dan reliabilitassebanyak 30 sampel dengan menggunakan software SPSS.2mm] Metode penelitian yang digunakan adalah analisis regresi berganda danregresi sederhana, uji f, uji t, dan koefisien determinasi. Dari hasil penelitian ini,dapat disimpulkan bahwa indikator-indikator dari variabel technology acceptancemodel yaitu perceived quality of e-shopping dan attitude berpengaruh positifterhadap variabel kepercayaan, dan indikator dari variabel kepercayaan yaitupengalaman (experienced), kualitas kerja (quality of work), dan kecerdasan(intelligence) berpengaruh positif terhadap variabel keputusan pembelian.Kata kunci: Social Media, Technology Acceptance Model, Trust, KeputusanPembelian, Instagram